The Drosophila STE20-like kinase misshapen is required downstream of the frizzled receptor in planar polarity signaling. - Paricio, N.; Feiguin, F.; Boutros, M.; Eaton, S.; Mlodzik, M. (The EMBO Journal, 1999)
The Drosophila misshapen (msn) gene is a member of the STE20 kinase family. We show that msn acts in the Frizzled (Fz) mediated epithelial planar polarity (EPP) signaling pathway in eyes and wings. Both msn loss- and gain-of-function result in defective ommatidial polarity and wing hair formation. Genetic and biochemical analyses indicate that msn acts downstream of fz and dishevelled (dsh) in the planar polarity pathway, and thus implicates an STE20-like kinase in Fz/Dsh-mediated signaling. This demonstrates that seven-pass transmembrane receptors can signal via members of the STE20 kinase family in higher eukaryotes. We also show that Msn acts in EPP signaling through the JNK (Jun-N-terminal kinase) module as it does in dorsal closure. Although at the level of Fz/Dsh there is no apparent redundancy in this pathway, the downstream effector JNK/MAPK (mitogen-activated protein kinase) module is redundant in planar polarity generation. To address the nature of this redundancy, we provide evidence for an involvement of the related MAP kinases of the p38 subfamily in planar polarity signaling downstream of Msn.